SALIVA IRON AND FERRITIN LEVELS IN PATIENTS WITH THALASSEMIA AND IRON DEFICIENCY ANEMIA - Duran Canatan; Sevgi Kosaci Akdeniz (Mediterranean Journal of Hematology and Infectious Diseases, 2012)
Most of the  techniques for measuring iron accumulation such as serum iron concentration, iron binding capacity, serum ferritin level, liver biopsy are invasive and hard methods for patients. The changes in trace element concentrations in saliva at different systemic diseases shows the quantity of the element at the body. The aim of this study was to compare the levels of iron and ferritin in saliva and serum in patients  with thalassemia and iron deficiency anemia. For this purpose, 35 healthy children as control group and 71 thalassemia major, 10 thalassemia intermedia and 15 thalassemia trait patients were involved. Their saliva  and serum iron and ferritin levels were measured.  There was no statistically difference between age and gender in all groups and control group (p>0.05).  In all groups saliva iron levels are higher than serum iron levels(p<0.05). Furthermore there was a positive correlation betwen serum and saliva  iron levels in thalassemia major, intermedia and trait groups ( p=0.000, r=0.972, r=0.720, r=0.955) and also there was a positive correlation between serum and saliva iron levels in control and iron deficiency group (p= 0.000, r= 0.885, r= 0.368).  In conclusion,  Saliva iron and ferritin levels increase  as well as serum in patients with thalassemia and decrease in patients with iron deficiency anemia. Saliva can be used for diagnosis routinely  to shows the iron overload  and deficiency of the body and its easy applicability and also a non-invasive procedure is important advantage.